2020
DOI: 10.3390/polym12051020
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Anion-Conducting Ionomer Fibers—Effect of Humidity on Final Properties

Abstract: Anion-conducting ionomer-based nanofibers mats are prepared by electrospinning (ES) technique. Depending on the relative humidity (RH) during the ES process (RHES), ionomer nanofibers with different morphologies are obtained. The effect of relative humidity on the ionomer nanofibers morphology, ionic conductivity, and water uptake (WU) is studied. A branching effect in the ES fibers found to occur mostly at RHES < 30% is discussed. The anion conductivity and WU of the ionomer electrospun mats prepared at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 68 publications
(85 reference statements)
2
6
0
Order By: Relevance
“…Branching effect was also observed by Halabi et al. [ 75 ] in the case of a ionomer, a quaternary ammonium functionalized aromatic poly (p‐phenylene oxide))‐based polymer, electrospun in DMF. In this case, branching occurred at RH ≤ 30% with much more branches at 30% than at 20%.…”
Section: Effect Of Humidity At the Scale Of The Fibersupporting
confidence: 64%
See 1 more Smart Citation
“…Branching effect was also observed by Halabi et al. [ 75 ] in the case of a ionomer, a quaternary ammonium functionalized aromatic poly (p‐phenylene oxide))‐based polymer, electrospun in DMF. In this case, branching occurred at RH ≤ 30% with much more branches at 30% than at 20%.…”
Section: Effect Of Humidity At the Scale Of The Fibersupporting
confidence: 64%
“…These processing conditions (i.e., low RH and addition of cations) were thus ideal to insure a high level of charges at the surface of the primary jet which is necessary for the emanation of secondary jets resulting finally to the fabrication of branched PVDF fibers. Branching effect was also observed by Halabi et al [75] in the case of a ionomer, a quaternary ammonium functionalized aromatic poly (p-phenylene oxide))-based polymer, electrospun in DMF. In this case, branching occurred at RH ≤ 30% with much more branches at 30% than at 20%.…”
Section: Branched Fiberssupporting
confidence: 63%
“…In addition, the ionomer concentration of 38 wt % and RH of 40% also ensured smooth and uniform fiber formation. 65 From the surface morphology of the membrane (Figure 2b), it was observed that the membrane was dense, which guaranteed the low gas permeability, and a fiber network could be observed on the surface. There was no QPPONF identified from the fracture surface of the composite membrane (Figure 2c), indicating a very good compatibility between QPPONNF and the PVA matrix, which was crucial for the mechanical property and ion conductivity of the membrane.…”
Section: Resultsmentioning
confidence: 94%
“…This type of functional coated layer is frequently employed as a feature in optical fiber sensors. A functional group of materials portrays a chemical or physical reaction with a purpose, for example, a small molecular structure grown layer-by-layer via deposition, or solution coating manufacture of a polymolecular structure by sol–gel or dip coating [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%